(untitled) (International Journal of Engineering and Computer Science, 2013)
This paper is used to express the great capabilities of the wireless power transmission techniques. Wireless power transfer allows a convenient, easy to use battery charging of mobile phones and other mobile devices. No hassle with cables and plugs, just place the device on a pad and that’s it. Such a system even has the potential to become a standard charging solution . I. Introduction: Usage of Wireless power provides a convenient solution for the users of portable devices and also gives designers the ability to develop more creative answers to problems. Inductive coupling is the method by which efficient and versatile wireless power can be achieved. It is a technology which can be developed to great potential and which has the proficiency to change the way power is transferred between devices and the source. Therefore, in 2009 the Wireless Power Consortium was founded with meanwhile more than 80 international companies as members. The consortium recently released the first worldwide standard on wireless power for mobile devices of to 5W called “Qi”. The contribution presents details of this standard and the rationale behind.